2015
DOI: 10.2166/wst.2015.302
|View full text |Cite
|
Sign up to set email alerts
|

Malachite green bioremoval by a newly isolated strain Citrobacter sedlakii RI11; enhancement of the treatment by biosurfactant addition

Abstract: Citrobacter sedlackii RI11, isolated from acclimated textile effluent after selective enrichment on synthetic dyes, was assessed for malachite green (MG) biotreatment potency. Results indicate that this bacterium has potential for use in effective treatment of MG contaminated wastewaters under shaking conditions at neutral and alkaline pH value, characteristic of typical textile effluents. Also, the newly isolated strain can tolerate higher doses of dye and decolorize up to 1,000 mg/l of dye. When used as micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Furthermore, the textile dye-decolorization effect achieved in the presence of microorganisms could be improved by producing biological surfactants. Mnif et al (2015) reported that lipopeptides derived from Bacillus subtilis SPB1 maximize the decolorization efficiency and accelerate the decolorization rate when the optimal concentrations of biosurfactants are approximately 0.075%. It is essential to summarize the influence of each parameter associated with biodegradation to develop a more effective and faster bacterial degradation method.…”
Section: Biological Methods (Fungal Decolorization and Microbial Enzy...mentioning
confidence: 99%
“…Furthermore, the textile dye-decolorization effect achieved in the presence of microorganisms could be improved by producing biological surfactants. Mnif et al (2015) reported that lipopeptides derived from Bacillus subtilis SPB1 maximize the decolorization efficiency and accelerate the decolorization rate when the optimal concentrations of biosurfactants are approximately 0.075%. It is essential to summarize the influence of each parameter associated with biodegradation to develop a more effective and faster bacterial degradation method.…”
Section: Biological Methods (Fungal Decolorization and Microbial Enzy...mentioning
confidence: 99%
“…When used as microbial surfactant to enhance MG biodecolorization, Bacillus subtilis SPB1derived lipopeptide accelerated the decolorization rate and maximized the decolorization efficiency at an optimal concentration of biosurfactant of about 0.075%. Studies ensured that MG removal by this strain could be due to biodegradation and/or adsorption [27].…”
Section: Biological Methodsmentioning
confidence: 99%
“…Thus, several studies have conducted to sort out an ecological solution to decrease its effect on water resources. Different biological or physicochemical solutions have been used to eliminate distinct contaminants such as pesticides, dyes, heavy metals and other organic matters from water and wastewater as microbiological decolorization [5] chemical precipitation [6] ion-exchange, adsorption, coagulation-flocculation and photocatalytic degradation [7]. These methods have obvious shortcomings, especially the high cost.…”
Section: Pathan Et Al 2021 Adsorption Potential Of Saccharum Bengalen...mentioning
confidence: 99%